Leverage and its impact on sector share prices Insurance, services and investment (An analytical study on the Baghdad Stock Exchange for the period 2012-2016) - Sina Ahmed Jarallah; Alaa Yahya Younus (International Journal of Psychosocial Rehabilitation, 2020)
This research aimed to shed light on the relationship of leverage, and the percentage of shares used in companies listed on the Baghdad Stock Exchange and its various sectors, and the Baghdad Stock Exchange is considered one of the main economic engines in Iraq, as the economic development thrives securities. To in the presence of an advanced market for achieve that, an analytical and applied study was conducted on some of the companies listed in this market, through the movement of stock prices for a sample of (12) companies for the period from (2012 2016). Among the most important results of these analyzes, a significant relationship was found between the prices of Stocks, and the percentage of leverage in the services, industry and investment sectors, in addition to that the results showed a significant relationship between stock prices and the rest of the variables which was (financial leverage, cash dividends, important earnings per share, company size), and the most recommendations that resulted from the research are , The necessity of paying attention to following up the percentage of financial leverage for companies and maintaining the level of earnings per share and maximizing it.